A Self-Monitoring Intervention to Improve the Self-Determination of Individuals With Intellectual and Developmental Disability in a Postsecondary Educational Program. (June 2023) - Randall, Kristina N.; Ryan, Joseph B.; Hirsch, Shanna E.; Allen, Abigail A.
Self-determination skills are critical for improving life outcomes for individuals with intellectual or developmental disabilities (IDD). The recent growth of postsecondary education (PSE) programs for those with IDD has provided additional opportunities for teaching self-determination skills. This study used a multiple probe across participants design with six individuals with IDD. The intervention consisted of a self-determination choice-making curriculum along with the use of a self-monitoring checklist to increase self-determination skills. Data were analyzed using visual analysis. Results revealed gains in participants' knowledge of choice-making steps with moderate effect size gains. Implications for practice and future research are discussed.